High-entropy O2 type layered oxide positive electrode material and preparation method and application thereof

The O2-type high-entropy layered oxide positive electrode material was prepared by high-temperature calcination method and ion exchange method, which solved the problem of limited ability of O3-type structure to suppress transition metal migration, and improved the capacity, cycle performance and rate performance of lithium-ion batteries.

CN119911985APending Publication Date: 2025-05-02XI AN JIAOTONG UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510117477.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The O3-type structure of the positive electrode material of existing lithium-ion batteries has limited ability to suppress transition metal migration, resulting in weak capacity and cycling performance of lithium-ion batteries.

Method used

The P2-type sodium-containing layered oxide was prepared by high-temperature calcination method, and the element composition and proportion were adjusted by ion exchange method to construct the O2-type high-entropy layered oxide positive electrode material.

Benefits of technology

It improves the capacity and circulation performance of lithium-ion batteries, enhances the rate performance and stability, and is simple and easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911985A_ABST
    Figure CN119911985A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy O2 type layered oxide positive electrode material and a preparation method and application thereof, and belongs to the technical field of preparation of lithium ion battery positive electrode materials. A P2 type high-entropy layered oxide is constructed by adjusting the element composition and proportion of a P2 type sodium-containing layered oxide, and then layered oxides (Lim[ LixNiyCozTMwMn1-x-y-z-w) O2 with different structures, namely the high-entropy O2 type layered oxide positive electrode material, are prepared by using a Li / Na ion exchange method. The method is simple in process and easy to operate, the material structure is stable and reliable, the lithium ion battery positive electrode materials with different layered structures can be effectively prepared, and industrialization popularization is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery positive electrode material preparation, and specifically relates to a high entropy O2 type layered oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] Energy storage batteries are crucial to solving the energy and environmental problems facing human society. Among all types of batteries, lithium-ion batteries have been widely used in electric vehicles, portable electronic devices, robots and other power tools and electronic devices due to their high energy density and no memory effect. Among various lithium-ion battery components, the positive electrode occupies the highest cost and is expensive, which has a great impact on the cost and overall performance of lithium-ion batteries. Therefore, the development of positive electrode materials is the key to the success of lithium-ion batteries. Lithium-ion battery positive electrode materials mainly include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium iron phosphate (LiFePO4), ternary lithium nickel cobalt manganese oxide Li(Ni, Co, Mn)O2, etc. Ternary lithium nickel cobalt manganese oxide Li(Ni, Co, Mn)O2 can be balanced and regulated in terms of specific energy, cyclability, safety and cost, and has received widespread attention. However, due to the irreversible migration of transition metals (TM) in the layered structure during charging and discharging, the layered structure gradually decays into partially disordered oxides, resulting in severe voltage and capacity decay and poor rate performance, which hinders its practical application.

[0003] High entropy oxides (HEOs) refer to single-phase oxides obtained by solid dissolving five or more metal or non-metal oxides in equal or near molar ratios. High entropy oxides are used as positive electrode materials with controllable composition, good ionic and electronic conductivity, and high structural stability. Therefore, high entropy materials have received widespread attention.

[0004] However, the structure of common high-entropy cathode materials is a thermodynamically stable O3 structure, which has limited ability to inhibit TM migration. Therefore, improving the capacity and cycle performance of lithium-ion batteries by coupling and regulating the stacking arrangement of oxygen and the high-entropy configuration has become a research focus. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high-entropy O2-type layered oxide positive electrode material and a preparation method and application thereof, so as to solve the technical problem that the material prepared by the prior art has an O3-type structure and has limited ability to inhibit TM migration, resulting in poor capacity and cycle performance of lithium-ion batteries.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing an O2 type high entropy lithium ion battery positive electrode material, comprising: firstly preparing a P2 type sodium-containing layered oxide Na by a high temperature calcination method; m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2 (TM = any one or two elements among Ti, Nb, W, Mo, Mg, Fe, Al, Zr, Zn,, Y, or doped with non-metallic element B). m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2 and Li-containing eutectic salt are thoroughly mixed by grinding or ball milling or high-speed mixer. The mixture is then calcined, usually at 200-280 °C in air for several hours. Finally, the water-soluble salt (LiNO3, LiCl, NaNO3, NaCl, etc.) is washed clean by filtration or centrifugation, and the resulting product is dried at 100 °C to obtain various O2-type layered high entropy cathode materials Li m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2; where 0.50≤ m ≤1.00,0.00≤ x ≤0.20; 0.00≤ y ≤0.32; 0.00≤ z ≤0.90; 0.00≤ w ≤0.10.

[0007] Preferably, the method for preparing an O2 type high entropy lithium ion battery positive electrode material comprises the following steps: Step 1. Weighing: According to the chemical formula Na m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2(0.5≤ m ≤1.0), weigh Ni, Mn, Co and corresponding transition metal oxides, non-metallic element dopants, and sodium-containing compounds, the molar ratio of sodium element to transition metal element is 1:(1.00-1.50), and mix them evenly.

[0008] Step 2. Calcination: The mixed sample in step 1 was placed in a muffle furnace and calcined at 800-900 °C for 8-12 h in an air atmosphere at normal pressure with a heating rate of 5-10 °C / min. The sample was naturally cooled to room temperature to obtain a P2-type sodium-containing layered oxide Na m [Li x Ni y Co z TM w Mn 1-x-y-z ]O2.

[0009] Step 3. Ion exchange: According to Li + and Na + The molar ratio of Li to Li is 1:1 to 5:1. A specific content of Li-containing eutectic salt is weighed; the P2-type sodium-containing layered oxide Na prepared in step 2 is m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2 is mixed evenly with lithium-containing Li eutectic salt and calcined for several hours in air at low temperature.

[0010] Step 4. Washing: After the calcination reaction is completed, the ion exchange product is obtained. Then, it is filtered or centrifuged, and the impurities produced by the reaction are washed away with deionized water, and washed with anhydrous ethanol 2 to 3 times, and the resulting product is dried and collected to obtain the lithium ion layered oxide Li m [Li x Ni y Co z TM w Mn 1-x-y-z ]O2.

[0011] A better technical solution of the present invention is: Furthermore, the transition metal oxides described in step 1 include TiO2, Nb2O5, WO3, MoO2, MgO, Fe2O3, Al2O3, ZrO2, ZnO, Y2O5, etc., and the non-metallic element dopant is H3BO3.

[0012] Furthermore, the Mn oxide in step 1 is any one of MnO2, Mn3O4 or Mn2O3; the Co-containing oxide is any one of CoO, Co2O3 or Co3O4.

[0013] Furthermore, the sodium-containing compound in step 1 is any one of Na2CO3, NaNO3, NaCl, NaCH3COO or NaOH.

[0014] Furthermore, the Li-containing eutectic salt in step 3 is any one of LiNO3 / LiCl, LiNO3 / LiOH, LiOH / KOH, LiNO3 / LiI, LiCl / LiBr, LiI / KI, LiCl / KCl and the like, and the mass ratio of the Li-containing eutectic salt is 80% / 20% to 90% / 10%; Furthermore, the calcination time in step 3 is 4 to 8 hours; Furthermore, the calcination temperature in step 3 is 200-280°C; Furthermore, the mixing method described in step 3 includes grinding, ball milling, high-speed mixer mixing, etc.; Furthermore, the amount of deionized water used for washing in step 4 is 1:15 g / ml.

[0015] The invention also discloses the application of the above-mentioned O2 type high entropy lithium ion battery positive electrode material in the preparation of lithium ion batteries.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the high entropy O2-type layered oxide positive electrode material disclosed in the present invention is based on an ion exchange strategy, adopts an ion exchange method at low temperature, constructs a P2-type high entropy layered oxide by adjusting the element composition and ratio of the P2-type sodium-containing layered oxide, and then uses a Li / Na ion exchange method to prepare layered oxides with different structures (Li m [Li x Ni y Co z TM w Mn 1-x-y-z ]O2 is a high entropy O2 type layered oxide positive electrode material.

[0017] Furthermore, the method can prepare two types of O2-type high-entropy layered manganese-based oxides, manganese-based and cobalt-based, by adjusting the composition and ratio of the oxides; Furthermore, by regulating different elements, etc., layered positive electrode materials with different needs can be prepared in a targeted manner. For example, by doping with active elements, the capacity can be improved; by doping with elements with large ion radius, the rate performance can be effectively improved; and by doping with elements with consistent TM ion radius, stability can be achieved.

[0018] Furthermore, by regulating the calcination temperature and time, the crystal particle size can be effectively controlled and the size distribution can be uniform. The size of the prepared single crystal oxide is between 2 and 10 microns, and the size of the prepared secondary spherical oxide is between 10 and 20 microns.

[0019] This method can not only prepare manganese-based metastable O2-type layered oxides, but also prepare cobalt-based metastable O2-phase layered structures, which have the advantages of low cost and high energy density. The oxide particles prepared by this method are not only composed of micron-sized single crystal particles with a grain size distribution between 2 and 10 microns, but also spherical secondary particles with a size distribution range of 10 to 20 microns. The distributed particle size is controllable, the consistency is good, it has excellent cycle stability, and a wide range of application (4.3 to 4.8V), which can be widely used in the electronic products and power battery markets.

[0020] The layered cathode material prepared by the method of the present invention has unique structural characteristics and excellent electrochemical performance, uniform distribution of crystal particles, controllable particle size, good batch uniformity, and the method is simple in process, easy to operate, and the material structure is stable and reliable. m [Li x Ni y Co z TM w Mn 1-x-y-z ]O2 is used as a template to effectively prepare lithium-ion battery positive electrode materials with different layered structures, and is easy to promote industrialization. The present invention is generally applicable to various layered lithium-embedded oxides with ideal structures and morphologies, providing potential opportunities for the design and development of lithium-ion battery positive electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the X-ray diffraction spectrum of the O2-type layered positive electrode material prepared in Example 1 of the present invention; Figure 2 The first charge-discharge curve of the O2-type layered cathode material prepared in Example 1 of the present invention at a rate of 0.1 C; Figure 3 The rate performance of the O2-type layered cathode material prepared in Example 1 of the present invention; Figure 4 The cycle performance of the O2-type layered cathode material prepared in Example 1 of the present invention; Figure 5 This is a scanning electron microscope image of the O2-type layered positive electrode material prepared in Example 2 of the present invention; Figure 6 The first charge-discharge curve of the O2-type layered cathode material prepared in Example 2 of the present invention at a rate of 0.1 C; Figure 7 The cycle performance of the O2-type layered cathode material prepared in Example 2 of the present invention; Figure 8 This is a scanning electron microscope image of the O2-type layered positive electrode material prepared in Example 3 of the present invention; Fig. 9This is the X-ray diffraction spectrum of the O2-type layered positive electrode material prepared in Example 3 of the present invention; Fig.10 The first charge-discharge curve of the O2-type layered cathode material prepared in Example 3 of the present invention at a 1 C rate; Fig.11 This is a scanning electron microscope image of the O2-type layered positive electrode material prepared in Example 4 of the present invention; Fig.12 The cycle performance of the O2-type layered cathode material prepared in Example 4 of the present invention; Fig.13 This is the X-ray diffraction spectrum of the O2-type layered positive electrode material prepared in Example 5 of the present invention; Fig.14 The first charge-discharge curve of the O2-type layered cathode material prepared in Example 5 of the present invention at a 1 C rate; Fig.15 This is the X-ray diffraction spectrum of the O2-type layered positive electrode material prepared in Example 6 of the present invention; Fig.16 This is the rate performance of the O2-type layered positive electrode material prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 In this embodiment, according to the chemical formula Li[Li0.20 Ni 0.17 Zn 0.02 Fe 0.01 Mn 0.60 ]O2 ingredients.

[0025] A method for preparing an O2 type high entropy lithium ion battery positive electrode material comprises the following steps: Step 1. Weighing: The corresponding salts and oxides such as Na2CO3, LiOH, NiO, ZnO, Fe2O3, Mn2O3 were weighed according to the molar ratio of sodium, lithium, nickel, zinc, iron and manganese elements of 10:2:1.7:0.2:0.1:6, and they were ground in a mortar and mixed evenly.

[0026] Step 2. Calcination: The mixed materials were heated to 800 °C at a rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain P2-type sodium-containing layered oxide Na[Li 0.20 Ni 0.17 Zn 0.02 Fe 0.01 Mn 0.60 ]O2.

[0027] Step 3. Ion exchange: According to Li + and Na + The molar ratio of LiNO3 / LiCl is 1:4. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0028] Step 4. Washing: The obtained product is filtered or centrifuged, the impurities produced by the reaction are washed away with deionized water, and then washed with ethanol for 2 to 3 times, and the obtained product is dried and collected to obtain the lithium ion layered oxide Li[Li 0.20 Ni 0.17 Zn 0.02 Fe 0.01 Mn 0.60 ]O2.

[0029] The charging and discharging performance test process of the positive electrode material prepared in this embodiment is as follows: The electrochemical performance tests conducted by the present invention all used self-assembled CR2032 button batteries; Weigh a certain amount of the positive electrode material, acetylene black, and binder polyvinylidene fluoride (PVDF) prepared in this embodiment in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) to make a slurry, the amount of NMP used is 30 times that of PVDF, and evenly coat it on aluminum foil. At 80 ° C, vacuum dry it for 12 hours, and then cut it into a pole piece with a diameter of 12 mm with a mold; the metal lithium sheet is used as the negative electrode, Celgard 2500 commercial polypropylene film is used as the diaphragm, and the electrolyte is 1 M LiPF6 EC+DEC (volume ratio 1:1) / FEC=95%:5% solution, and the battery is assembled in an argon-filled glove box. After standing for 2 hours, the battery was tested for electrochemical performance, with a voltage range of 2.0-4.8 V, and the first cycle charge and discharge and cycle performance tests were carried out at a current density of 0.1 C. The rate performance tests were 0.1 C, 0.5 C, 1 C, 3 C, etc.

[0030] XRD results show that the Li[Li 0.20 Ni 0.17 Zn 0.02 Fe 0.01 Mn 0.60 ]O2 is the O2 structure, such as Figure 1 shown. Figure 2 It is Li[Li 0.20 Ni 0.17 Zn 0.02 Fe 0.01 Mn 0.60 ]O2's first charge and discharge curve, the first cycle discharge capacity is above 220mAh / g ( Figure 2 ). Figure 3 As for the rate performance, it can still maintain 160 mAh / g at 3 C, and the rate performance is excellent. Figure 4 It is Li[Li 0.20 Ni 0.17 Zn 0.02 Fe 0.01 Mn 0.60 ]The cycle performance diagram of O2 shows that after 50 cycles, the capacity retention rate is above 90%.

[0031] Example 2 In this embodiment, according to the chemical formula Li[Li 0.20 Ni 0.17 Co 0.01 Mg 0.02 Mn 0.60 ]O2 ingredients.

[0032] A method for preparing an O2 type high entropy lithium ion battery positive electrode material comprises the following steps: Step 1. Weighing: The corresponding salts and oxides such as Na2CO3, LiOH, NiO, Co3O4, MgO, and Mn3O4 were weighed according to the molar ratio of sodium, lithium, nickel, cobalt, magnesium, and manganese elements of 10:2:1.7:0.1:0.2:6, and they were ground in a ball mill and mixed evenly.

[0033] Step 2. Calcination: The mixed materials were heated to 800 °C at a rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain P2-type sodium ion layered oxide Na[Li 0.20 Ni 0.17 Co 0.01 Mg 0.02 Mn 0.60 ]O2.

[0034] Step 3. Ion exchange: According to Li + and Na + The molar ratio of LiNO3 / LiCl is 1:2. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0035] Step 4. Washing: The obtained product is filtered or centrifuged, the impurities produced by the reaction are washed away with deionized water, and then washed with ethanol for 2 to 3 times, and the obtained product is dried and collected to obtain the lithium ion layered oxide Li[Li 0.20 Ni 0.17 Co 0.01 Mg 0.02 Mn 0.60 ]O2.

[0036] The layered oxide Li[Li 0.20 Ni 0.17 Co 0.01 Mg 0.02 Mn 0.60 ]The microscopic morphology of O2 is shown in Figure 5 , it can be seen from the figure that the layered oxide obtained is spherical particles of 17 μm.

[0037] The charge and discharge performance test of the positive electrode material prepared in this embodiment: The test method is the same as that in Example 1. The results show that the first discharge capacity of the O2-type lithium-ion layered positive electrode material prepared in this embodiment at 0.1 C is 256 mAh / g. Figure 6 After 30 cycles, the capacity retention rate is 86%. Figure 7 .

[0038] Example 3 In this embodiment, according to the chemical formula Li[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]O2 ingredients.

[0039] A method for preparing an O2 type high entropy lithium ion battery positive electrode material comprises the following steps: Step 1. Weighing: The corresponding salts, acids and oxides such as Na2CO3, Co3O4, ZrO2, ZnO, TiO2 and H3BO3 were weighed according to the molar ratio of sodium, cobalt, zirconium, zinc, titanium and boron elements of 10:9:0.1:0.2:0.1:0.6, and they were ground and mixed evenly in a high-speed mixer.

[0040] Step 2. Calcination: The mixed materials were heated to 800 °C at a rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain P2-type sodium ion layered oxide Na[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]O2.

[0041] Step 3. Ion exchange: According to Li + and Na + The molar ratio of LiNO3 / LiCl is 1:2. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0042] Step 4. Washing: The obtained product is filtered or centrifuged, the impurities generated by the reaction are washed away with deionized water, and then washed with ethanol for 2 to 3 times, and the obtained product is dried and collected to obtain the lithium ion layered oxide Li[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]O2.

[0043] The Li[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]The microscopic morphology of O2 is shown in Figure 8 From the figure, we can see that the prepared layered oxide has a flaky structure and is a single crystal particle with a uniform particle size distribution between 2.1 and 6.5 μm. The XRD diagram shows that it is an O2 structure. Fig. 9 .

[0044] Charge and discharge performance test: The test method is the same as that of Example 1, but the test conditions are different. The voltage range is 3.0-4.65 V and the current density is 1 C. The results show that the first discharge capacity of the positive electrode material prepared in this example at 1 C is 242 mAh / g. Fig.10 shown.

[0045] Example 4 In this embodiment, according to the chemical formula Li[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]O2 ingredients.

[0046] Step 1. Weighing: The corresponding salts, acids and oxides such as Na2CO3, Co3O4, ZrO2, ZnO, TiO2 and H3BO3 were weighed according to the molar ratio of sodium, cobalt, zirconium, zinc, titanium and boron elements of 10:9:0.1:0.2:0.1:0.6, and they were ground and mixed evenly in a high-speed mixer.

[0047] Step 2. Calcination: The mixed materials were heated to 900 °C at a rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain P2-type sodium ion layered oxide Na[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]O2.

[0048] Step 3. Ion exchange: According to Li + and Na + The molar ratio of LiNO3 / LiCl is 1:2. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0049] Step 4. Washing: The obtained product is filtered or centrifuged, the impurities generated by the reaction are washed away with deionized water, and then washed with ethanol for 2 to 3 times, and the obtained product is dried and collected to obtain the lithium ion layered oxide Li[Co0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]O2.

[0050] The Li[Co 0.90 Zr 0.01 Zn 0.02 Ti 0.01 B 0.06 ]The microscopic morphology of O2 is shown in Fig.11 ,From the figure, it can be seen that the O2 type lithium ion layered oxide particles are about 5 μm in size and have a uniform size distribution.

[0051] Charge and discharge performance test: The test method is the same as that of Example 3, except that the voltage range is 3.0-4.6 V. The positive electrode material prepared in this example has an initial discharge capacity of 214 mAh / g at 1 C, and a capacity retention rate of 94% after 25 cycles. Fig.12 shown.

[0052] Example 5 In this embodiment, according to the chemical formula Li[Co 0.91 Zr 0.01 Zn 0.03 Ti 0.02 Ni 0.04 ]O2 ingredients.

[0053] A method for preparing an O2 type high entropy lithium ion battery positive electrode material comprises the following steps: Step 1. Weighing: The corresponding salts and oxides such as Na2CO3, Co3O4, ZrO2, ZnO, TiO2, NiO were weighed according to the molar ratio of sodium, cobalt, zirconium, zinc, titanium and nickel elements of 10:9.1:0.1:0.3:0.2:0.4, and they were ground and mixed evenly in a high-speed mixer.

[0054] Step 2. Calcination: The mixed materials were heated to 800 °C at a rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain P2-type sodium ion layered oxide Na[Co 0.91 Zr 0.01 Zn 0.03 Ti 0.02 Ni 0.04 ]O2.

[0055] Step 3. Ion exchange: According to Li + and Na +The molar ratio of LiNO3 / LiCl is 1:2. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0056] Step 4. Washing: The obtained product is filtered or centrifuged, the impurities generated by the reaction are washed away with deionized water, and then washed with ethanol for 2 to 3 times, and the obtained product is dried and collected to obtain the lithium ion layered oxide Li[Co 0.91 Zr 0.01 Zn 0.03 Ti 0.02 Ni 0.04 ]O2.

[0057] The Li[Co 0.91 Zr 0.01 Zn 0.03 Ti 0.02 Ni 0.04 ]XRD of O2 Fig.13 , it can be seen from the figure that Li[Co 0.91 Zr 0.01 Zn 0.03 Ti 0.02 Ni 0.04 ]O2 is O2 structure.

[0058] Charge and discharge performance test: The test method is the same as that of Example 3. The first discharge capacity of the positive electrode material prepared in this example at 1 C is 233 mAh / g. Fig.14 shown.

[0059] Example 6 In this embodiment, according to the chemical formula Li[Co 0.90 Zr 0.02 Zn 0.03 Ti 0.01 B 0.04 ]O2 ingredients.

[0060] Step 1. Weighing: The corresponding salts, acids and oxides such as Na2CO3, Co3O4, ZrO2, ZnO, TiO2 and H3BO3 were weighed according to the molar ratio of sodium, cobalt, zirconium, zinc, titanium and boron elements of 10:9:0.2:0.3:0.1:0.4, and they were ground and mixed evenly in a high-speed mixer.

[0061] Step 2. Calcination: The mixed materials were heated to 800 °C at a rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain P2-type sodium ion layered oxide Na[Co 0.90 Zr 0.02 Zn 0.03 Ti 0.01 B 0.04 ]O2.

[0062] Step 3. Ion exchange: According to Li + and Na + The molar ratio of LiNO3 / LiCl is 1:2. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0063] Step 4. Washing: The obtained product is filtered or centrifuged, the impurities generated by the reaction are washed away with deionized water, and then washed with ethanol for 2 to 3 times, and the obtained product is dried and collected to obtain the lithium ion layered oxide Li[Co 0.90 Zr 0.02 Zn 0.03 Ti 0.01 B 0.04 ]O2.

[0064] The Li[Co 0.90 Zr 0.02 Zn 0.03 Ti 0.01 B 0.04 ]XRD of O2 Fig.15 , it can be seen from the figure that all the diffraction peaks belong to the O2 type layered structure.

[0065] Charge and discharge performance test: The test method is the same as that of Example 3, but the rate test conditions are different. The rate test conditions are 0.1, 0.2, 0.5, 1, 3, 5, and 10 C, and the voltage range is 3.0-4.6 V. The results show that the positive electrode material prepared in this example has an initial discharge capacity of 230 mAh / g at a rate of 0.1 C, and still has a capacity of 160 mAh / g at 10 C, which is much higher than the undoped O2-type comparative sample LiCoO2. Fig.16 .

[0066] Comparative Example In this comparative example, the ingredients are prepared according to the chemical formula LiCoO2.

[0067] A method for preparing an O2 type high entropy lithium ion battery positive electrode material comprises the following steps: Step 1. Weighing: Weigh the corresponding salts and oxides such as Na2CO3 and Co3O4 according to the molar ratio of sodium to cobalt element of 1:1, grind them in a mortar and mix them evenly.

[0068] Step 2. Calcination: The uniformly mixed material was heated to 800 °C at a heating rate of 5 °C / min in an air atmosphere at normal pressure, kept at this temperature for 12 h, and naturally cooled to room temperature to obtain a P2-type sodium-containing layered oxide NaCoO2.

[0069] Step 3. Ion exchange: According to Li + and Na + The molar ratio of LiNO3 / LiCl is 1:4. Weigh a specific content of Li-containing eutectic salt LiNO3 / LiCl; mix the P2-type sodium-containing layered oxide prepared in step 2 with the Li-containing eutectic salt, and the mass ratio of LiNO3 / LiCl is 88%:12%. Calcine at 280°C for 4 h.

[0070] Step 4. Washing: The obtained product is filtered or centrifuged, impurities generated by the reaction are washed away with deionized water, and washed with ethanol 2 to 3 times, and the obtained product is dried and collected, which is the lithium ion layered oxide LiCoO2.

[0071] The charging and discharging performance test process of the positive electrode material prepared in this comparative example is as follows: The electrochemical performance tests conducted by the present invention all used self-assembled CR2032 button batteries; Weigh a certain amount of the positive electrode material, acetylene black, and binder polyvinylidene fluoride (PVDF) prepared in this embodiment in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) to make a slurry, the amount of NMP used is 30 times that of PVDF, and evenly coat it on aluminum foil. At 80 ° C, vacuum dry it for 12 hours, and then cut it into a pole piece with a diameter of 12 mm with a mold; the metal lithium sheet is used as the negative electrode, Celgard 2500 commercial polypropylene film is used as the diaphragm, and the electrolyte is 1 M LiPF6 EC+DEC (volume ratio 1:1) / FEC=95%:5% solution, and the battery is assembled in an argon-filled glove box. After standing for 2 hours, the battery is tested for electrochemical performance. The voltage range is 3.0-4.6 V, and the rate performance tests are 0.1 C, 0.2 C, 0.5 C, 1 C, 3C, 5 C, 10 C, etc.

[0072] In summary, the present invention constructs a P2-type high-entropy layered oxide by adjusting the elemental composition and ratio of the parent Na-based precursor, and further uses the Li / Na ion exchange method to prepare an O2-type high-entropy cathode material. The ion exchange strategy can achieve efficient preparation of lithium-ion ternary cathode materials, which is conducive to the implementation of industrialization.

[0073] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a high entropy O2-type layered oxide positive electrode material, characterized in that: include: Preparation of P2-type sodium-containing layered oxides by high temperature calcination m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2, where TM is any one or two elements of Ti, Nb, W, Mo, Mg, Fe, Al, Zr, Zn and Y, or doped with non-metallic element B; 0.50≤ m ≤1.00,0.00≤ x ≤0.20; 0.00≤ y ≤0.32; 0.00≤ z ≤0.90; 0.00≤ w ≤0.10; P2-type sodium-containing layered oxide Na m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2 and the Li-containing eutectic salt are fully mixed to obtain a mixture; The mixture was calcined at 200-280 °C, and the calcined product was filtered, washed, and dried to obtain an O2-type layered high entropy cathode material Li m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2.

2. The method for preparing a high entropy O2-type layered oxide positive electrode material according to claim 1, characterized in that: The following steps are involved: 1) According to the chemical formula Na m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2, a transition metal oxide or a non-metallic element dopant, a sodium-containing compound, and one or more of Ni-containing oxide, Mn-containing oxide, and Co-containing oxide are mixed evenly, and then calcined at 800-900 ° C for 8-12 h, and naturally cooled to room temperature to obtain a P2-type sodium-containing layered oxide Na m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2; 2) According to Li + and Na + The molar ratio is 1:1 to 5:1, a Li-containing eutectic salt is taken, and the Li-containing eutectic salt and the P2-type sodium-containing layered oxide Na m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2 is mixed evenly, calcined at 200-280 °C for 4-8 hours, and then filtered, washed and dried to obtain the O2-type layered high entropy cathode material Li m [Li x Ni y Co z TM w Mn 1-w-x-y-z ]O2.

3. The method for preparing a high entropy O2-type layered oxide positive electrode material according to claim 2, characterized in that: In step 1), the molar ratio of sodium element to transition metal element is 1:(1.00-1.50).

4. The method for preparing a high entropy O2-type layered oxide positive electrode material according to claim 2, characterized in that: In step 1), the transition metal oxides include TiO2, Nb2O5, WO3, MoO2, MgO, Fe2O3, Al2O3, ZrO2, ZnO and Y2O5, and the non-metallic element dopant is H3BO3; the Mn-containing oxide uses MnO2, Mn3O4 or Mn2O3, the Co-containing oxide uses CoO, Co2O3 or Co3O4, the sodium-containing compound is Na2CO3, NaNO3, NaCl, NaCH3COO or NaOH; the Ni-containing oxide is NiO.

5. The method for preparing a high entropy O2-type layered oxide positive electrode material according to claim 2, characterized in that: In step 1), calcination is carried out in an air atmosphere at normal pressure with a heating rate of 5-10 °C / min.

6. The method for preparing a high entropy O2-type layered oxide positive electrode material according to claim 2, characterized in that: In step 2), the Li-containing eutectic salt is LiNO3 / LiCl, LiNO3 / LiOH, LiOH / KOH, LiNO3 / LiI, LiCl / LiBr, LiI / KI, LiCl / KCl, and the mass ratio of the two salts in the Li-containing eutectic salt is 80% / 20%~90% / 10%.

7. The method for preparing a high entropy O2-type layered oxide positive electrode material according to claim 2, characterized in that: In step 2), the filtration is performed by suction filtration or centrifugation, and the impurities generated by the reaction are first washed with deionized water, and then washed with anhydrous ethanol for 2 to 3 times.

8. A high entropy O2-type layered oxide positive electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The oxide particles of the high-entropy O2-type layered oxide positive electrode material are composed of micron-sized single crystal particles with a grain size distribution between 2 and 10 microns, and spherical secondary particles with a size distribution range between 10 and 20 microns.

9. Use of the high entropy O2-type layered oxide positive electrode material according to claim 8 in the preparation of positive electrode materials for lithium-ion batteries.

10. The use according to claim 9, characterized in that The prepared LiTMO2 has a capacity retention rate of over 90% after 50 cycles at 2.0-4.8 V and 0.1 C. The prepared LCO has a capacity of over 240 mAh / g at 3-4.65 V and 1 C, and a capacity retention rate of over 90% after 30 cycles.

Citation Information

Cited By

  • Composite sodium electric layered oxide positive electrode material and preparation method and application thereof

    CN121726396A